Use of Animal and Animal Products for Rheumatoid Arthritis Treatment: An Explorative Study in Odisha, India - Samal, Mousumi; Sahoo, Krushna Chandra; Pati, Sanghamitra; Tripathy, Saumya Ranjan; Parida, Manoj Kumar; Das, Bidyut Kumar (Frontiers in Medicine, 2020)
Severe fatigue, pain, disability, and wretchedness are a major concern for rheumatoid arthritis (RA). The experienced pain of the patients often forced them for medication decision with various indigenous substances including animals. However, there is little evidence on the use of animals as a traditional medicine in RA. Hence, this study explored the patients’ experience and perceptive towards the use of animals and animal products for the treatment of RA. A qualitative exploratory study was conducted at the out-patient rheumatology department of a tertiary care medical college hospital in Cuttack, Odisha, India. Total 18 In-depth Interviews were conducted among the RA patients those who used animals and animal products for RA treatment. The data were analyzed using content analysis. Four major categories emerged: 1) Prevailing traditional treatment of RA using animals, 2) Beliefs and values behind the traditional treatment of RA, 3) Indigenous empirical knowledge and traditional teachings on RA, and 4) Ethical aspects of the indigenous practice on RA. This study showed that the patients ate dead animals to get relief from the RA. However, there is hardly any perceived positive result of the treatment; which indicates the poor health-related quality of life among RA patients. Hence, community awareness, social mobilization, and advance screening tools would necessary to improve timely detection and prevention of irrational treatment practices among RA patients.